2013
DOI: 10.1155/2013/457865
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Carbon Nanoparticles Isolated from Natural Sources against Pathogenic Gram-Negative and Gram-Positive Bacteria

Abstract: This paper describes the isolation of carbon nanoparticles (CNPs) from kitchen soot, characterization of the CNPs by UV/visible spectroscopy, SEM and XRD, and their antimicrobial action. The antibacterial activity of the isolated carbon nanoparticles was tested against various pathogenic bacterial strains such as Gram-negative Proteus refrigere and Pseudomonas aeruginosa and Gram-positive Staphylococcus aureus and Streptococcus haemolyticus. The inhibition zones were measured, and it was found that the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…With the known popularity of carbon for its biocompatibility333, which was also tested and confirmed in case of the turmeric smudge derived NC@TS obtained in our study too, it definitely holds an edge to turmeric smoke. This study confirms that harvesting the NC@TS could lead to safer and effective extension of this age old smudging method to real time drug delivery and pharmaceutical applications.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…With the known popularity of carbon for its biocompatibility333, which was also tested and confirmed in case of the turmeric smudge derived NC@TS obtained in our study too, it definitely holds an edge to turmeric smoke. This study confirms that harvesting the NC@TS could lead to safer and effective extension of this age old smudging method to real time drug delivery and pharmaceutical applications.…”
Section: Discussionsupporting
confidence: 78%
“…10(f)); they trigger off a cascade of other attacks on the cytoplasm and organelles, resulting in cell death. It is also interesting to note here that Sheena et al 33,. have reported that kitchen soot derived carbon nanoparticles possessed inherent antibacterial property.…”
Section: Discussionsupporting
confidence: 60%
“…[39]. The additional peaks detected at 29.47° and 40.78° are attributed to the natural graphene-like carbon present in the ZnO-CuO nanocomposites [42] as carbon is a main phytochemical element in the leaves of the C. gigantea medicinal plant [43,44]. Natural carbon in binary ZnO-CuO nanocomposites could further enhance the synergic effect on antimicrobial activity [45,46].…”
Section: Time-kill Assaymentioning
confidence: 99%
“…Carbon NPs in particular fullerene, carbon nanotubes, graphene and diamond-like carbon structures have been employed for the development of new antimicrobial agents due to the high surface to volume ratio and their unique chemical and physical properties (Varghese et al, 2013). Investigations have revealed that as the size of carbon particles decreases right down to the nanoscale range, their antimicrobial activity will increase due to their larger surface area consistent with unit volume and high percentage of atoms in the surface and near-surface layers.…”
Section: Carbon Nps (C Nps)mentioning
confidence: 99%
“…Investigations have revealed that as the size of carbon particles decreases right down to the nanoscale range, their antimicrobial activity will increase due to their larger surface area consistent with unit volume and high percentage of atoms in the surface and near-surface layers. C NPs have been found to be effective against bacterial strains such as Pseudomonas aeruginosa and S. aureus (Varghese et al, 2013). Also, previous studies demonstrated the antimicrobial properties of singlewalled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT) against different pathogenic bacteria (E. coli, S. epidermidis, B. subtilis, S. aureus) (Kang et al, 2006).…”
Section: Carbon Nps (C Nps)mentioning
confidence: 99%